New Perspectives in Information Systems and Technologies, Volume 2 - Rocha, Álvaro; Correia, Ana Maria; Tan, Felix . B.; Stroetmann, Karl . A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book contains a selection of articles from The 2014 World Conference on Information Systems and Technologies (WorldCIST'14), held between the 15th and 18th of April in Funchal, Madeira, Portugal, a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges of modern Information Systems and Technologies research, technological development and applications. The main topics covered are: Information and Knowledge Management; Organizational Models and Information Systems; Intelligent and Decision Support Systems; Software Systems, Architectures, Applications and Tools; Computer Networks, Mobility and Pervasive Systems; Radar Technologies; Human-Computer Interaction; Health Informatics; and Information Technologies in Education.
From the Contents: Language Technology for e Government - Business Cases -- Using a Multi-criteria Approach in Early Warning Information System (MCEWIS) -- Evaluation of an integrated mobile payment, ticketing and couponing solution based on NFC -- Learning from the experience -- Systemic thinking for e-government development in developing countries: a question unsolved.
Keywords: Computational intelligence; Artificial intelligence; User interfaces (Computer systems).; Computational Intelligence; Artificial Intelligence; User Interfaces and Human Computer Interaction